La enseñanza aprendizaje de geometría analítica y el desarrollo del pensamiento lógico matemático - Becerra Montalván, Anthony Fernando (2025)
Mathematical logical thinking within the teaching-learning process contributes significantly to the students' reasoning, favors critical judgment regarding things that they observe. The objective of the research was to analyze the teaching-learning of analytical geometry in the development of mathematical logical thinking in students who have completed the second year of unified general baccalaureate. It had a mixed approach of non-experimental type with descriptive scope, with field design, survey method with the questionnaire as instrument. The results obtained show a traditional teaching with mostly magisterial strategies and seldom apply Cooperative Learning as a strategy, which influences the learning and degree of development of mathematical logical thinking of the students. Taking the study of conics as a reference, it is concluded that the development of mathematical logical thinking is limited since they do not manage to contextualize conics in real problems or to relate their empirical knowledge with theoretical knowledge much less to transform such problems into mathematical language.